Modification of Lifestyle Factors are Needed to Improve the Metabolic Health of Patients with Cardiovascular Disease Risk - Landini, Linda (Current Pharmaceutical Design, 2014)
Cardiovascular risk factors, irregardless of their assessment modalities, are based on cardiovascular health. Lifestyle influences metabolic profiles and these changes affect cardiovascular risk factors. Cardiovascular risk factors can be classified into three basic categories: 1. Predisposing risk factors (e.g., age, gender, medical history, and genetic factors); 2. Clinical and metabolic factors (e.g., hypertension, changes in lipid metabolism, diabetes mellitus, obesity, metabolic syndrome, homocysteine, serum uric acid concetntrations, and L-arginine dimethylated derivatives); 3. Modifying behavioral factors (e.g., cigarette smoking, high caloric diet, alcohol intake, sedentary life). Some of these factors are metabolic components of body metabolism because they act by metabolic reactions while others characterized by structural alterations of the cardiovascular system, at least initially, exert their harmful effects by metabolic substrates. Metabolic responses such as biochemical substances, drugs or others, that act initially as cardiovascular risk factors, identify that an early treatment of the altered parameters observed should be a useful approach to reduce the rate of heart attacks with a significant improvement in the outcome of cardiovascular disease.
Keywords: heart and blood vessel rate